In vitro plant regeneration from protocorms-like bodies (PLBs) and callus of Phalaenopsis gigantea (Epidendroideae: Orchidaceae) - Niknejad, Azadeh; Abdul Kadir, Mihdzar; Kadzimin, Saleh (Academic Journals, 2011)
Phalaenopsis, with long arching sprays of flowers, are among the most beautiful flowers in the world. Phalaenopsis is an important genus and one of the most popular epiphytic monopodial orchids, grown commercially for the production of cut flowers and potted plants. Most of them have different and interesting morphological characteristics which have different value to the breeders. Phalaenopsis gigantea is one of the most difficult to grow and has the potential of producing beautiful hybrids. An efficient and reproducible method for large-scale propagation of Ph. giganteausing leaf sections has been developed. Leaf sections from in vitro young plants were cultured on New Dogashima Medium (NDM) supplemented with cytokinins (6-Benzylaminopurine (BAP), Thidiazuron (TDZ), and Kinetin (KIN), each at 0.01, 0.1, 0.5 and 1.0 mg/L) alone and in combinations with (auxins a-naphthaleneacetic acid (NAA), at 0.01, 0.1, 0.5 and 1.0 mg/L). The explants developed calli and protocorm-like-bodies (PLBs) within 6 weeks of culture. Treatment TDZ in combination with auxins was found to be the best for the induction of callus and PLBs. In vitroregeneration of Ph. gigantea PLB was achieved by exposure to light and transferring to hormone free NDM solid medium.